The Vector - Host - Pathogen Interface: The Next Frontier in the Battle Against Mosquito-Borne Viral Diseases? - Onyango, Maria Gorreti; Ciota, Alexander T.; Kramer, Laura D. (Frontiers in Cellular and Infection Microbiology, 2020)
An unprecedented spread of mosquito-borne viruses and increasing populations of mosquito vectors has led to an increase in the frequency of mosquito-borne virus disease outbreaks. Recent outbreaks of Zika virus (ZIKV) and yellow fever virus (YFV), among others have led to a concerted effort to understand the biology of mosquito-borne viruses and their interaction with their vector mosquito and vertebrate hosts. Recent studies have aimed to understand the vector-host-pathogen interface and how it influences infection, tropism and disease severity in the vertebrate host. The initial replication of the pathogen at the skin bite site is crucial in determining the progression of the infection in the vertebrate host. Delineating the role of the commensal microbes in the mosquito saliva as well as how they interact with the vertebrate host keratinocytes will improve our understanding of disease immunopathology and may lead to new therapeutics.